Literature Study: Students' Misconceptions on Sound Waves - Tania; Bangun, Ayu Aprilla; Sinuraya, Oktaviani Pehulisa; Sitorus, Santa Anggryani; Fitri, Syah (Universitas Negeri Semarang, 2025)
Misconception is a mistake understand draft scientifically based on understanding the beginning of something material. The aim of this research is to explore what just misconceptions experienced students on the material wave sound and identify factor the cause, which can made into reference by prospective teachers for minimize misconceptions in students and to increase understanding students on the material wave sound. This research uses method fist literature, this study identifies and summarizes findings relevant research about misconceptions in material wave sound. Of the 10 articles analyzed, misconceptions in the sub- material propagation sound own percentage the largest (80%), misconception related material connection between fast propagation, frequency and length waves (70%), misconceptions about intensity sound and influence distance (60%), on the material Doppler effect (40%). overall this research can give contribution in identify misconceptions For repair quality from learning physics and reducing misconceptions in students.